What Matters More: Religious Values or Academic Excellence?A Conjoint Analysis of Parental Priorities in Islamic Education - Murti, Anjani Wira; Purwanto, P; Diharto, Awan Kostrad; Ramdhani, Deddy; Alauddin , Muhammad Badat (Suhuf: International Journal of Islamic Studies, 2025)
This study investigates parental preferences in selecting integrated Islamic educational institutions in Mataram, West Nusa Tenggara, particularly among career-oriented parents who face challenges in directly supervising their children’s education. The research aims to identify the most dominant attribute influencing parental preferences and to evaluate the extent to which these attributes contribute to the decision-making process. A quantitative method was employed using conjoint analysis. Data were collected from 100 mothers of kindergarten-aged children residing in Mataram, selected through quota sampling. A questionnaire was used for data collection, and the analysis was conducted using conjoint analysis with a multiple linear regression approach via SPSS. The results indicate that among six evaluated attributes; school quality, teacher quality, school image, service quality, location, and cost only teacher quality and school location significantly influence parental preferences. Among these, teacher quality emerged as the most dominant factor. Collectively, the six attributes accounted for 76.8% of the variance in parental preference, while the remaining 23.2% was influenced by factors outside the research model. These findings underscore the importance of teacher competence and accessibility in shaping school choice decisions, offering valuable insights for educational institutions aiming to attract and retain students through improved staffing and strategic location planning.